Social and ecological impacts after normalization of the Banjir Kanal Barat River for communities around North Semarang - Arina Hudaya; Lu’lu’ah Qothrunnada; Ahmad Fauzan Hidayatullah; Thiyas Tono Taufiq (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
In 2010, the Semarang government normalized the Banjir Kanal Barat River by dredging and widening the river and managing spatial planning by adding a waterfront. The purpose of normalization is to increase the water discharge capacity so that it can accommodate water flow from three rivers (the Kreo River, the Kripik River, and the Garang River). The focus of this study is to identify social and ecological impacts after the normalization of the BKB River. This study uses qualitative methods with data collection techniques carried out through observation, in-depth interviews, and documentation. The informants in this study numbered seven people, consisting of officers (managers of the BKB Weir and cleaning officers), RW heads, the community, and visitors. The results showed the impact on social aspects, namely that the community has new public spaces, brings economic opportunities, strengthens social solidarity through river mutual aid activities, and, after normalization, the BKB River area becomes prone to crime because the streets are quiet plus there is poor lighting. The ecological impact is the use of land on the banks of the BKB River for fish farming and agriculture. People’s behavior in seeing rivers is formed from the interactions they carry out at the individual level, so people have various perceptions in looking at the river, as mentioned above.